admin

2 months ago

Guest #9847970

2 months ago

Reduce your fraction 2/4 down to 1/2, and then find the smallest common factor of 2 and 6 (which happens to be 6). Since you multiply 2 by 3, then you have to multiply your numerator by 3 also, giving you 3/6. Since your denominators match, it means you have found the answer.

Guest #9847971

2 months ago

2/4 = x/6

2/4 = 1/2 = 3/6

you find the least common denominator which will be 12

2/4 = 6/12

you multiply 4 x 3 to get 12 so you have to multiply 2 x 3 and get 6.

now if you divide both numbers 6/12 by 2 then 6/12=1/2.

another way to look at this one is 2 is half of 4, so what is half of 6.

../.... = .../......

Question

You travel 60 kilometers in 1.5 hours. What is your average speed?

Solution 1

technically you could write 60km/1.5hr but I think you meant km/hr.

So your traveling 60km every 1.5hours but you only want to know how much every one hour. think of 1.5 as 150% of what you want (which is one) take 60 divide it into one hundred pieces (60/150) then multiply buy 100% of what you want (quotient of last problem * 100)

final equation looks like this (60/150) 100 = 40 km/ hr

Ps. *=multiply

So your traveling 60km every 1.5hours but you only want to know how much every one hour. think of 1.5 as 150% of what you want (which is one) take 60 divide it into one hundred pieces (60/150) then multiply buy 100% of what you want (quotient of last problem * 100)

final equation looks like this (60/150) 100 = 40 km/ hr

Ps. *=multiply

Solution 2

Your average speed is 60 km per 1.5 hours. In a somewhat more popular unit, it's 60/1.5=40 km/hr.

Question

f(x)={1/2x-2, if x≥0}

{3/4x+3, if x<0}

Graph this equation?

I don't understand how to do this.

{3/4x+3, if x<0}

Graph this equation?

I don't understand how to do this.

Solution 1

[tex]f(x)= \left\{\begin{array}{ccc}\frac{1}{2}x-2&if\ x\geq0\\\frac{3}{4}x+3&if\ x < 0\end{array}\right\\------------------\\x < 0\to f(x)=\frac{3}{4}x+3\\\\for\ x=-4\to y=\frac{3}{4}(-4)+3=-3+3=0\to(-4;\ 0)\\for\ x=0\to y=\frac{3}{4}(0)+3=3\to(0;\ 3)\\------------------------\\x\geq0\to f(x)=\frac{1}{2}x-2\\\\for\ x=0\to y=\frac{1}{2}(0)-2=-2\to(0;-2)\\for\ x=4\to y=\frac{1}{2}(4)-2=2-2=0\to(4;\ 0)\\------------------------------\\Look\ at\ the\ picture.[/tex]

Question

* Use for question 4-6 *

The expression 16t2 models the distance in feet that an object falls during t seconds after being dropped. Find the distance an object falls during each time.

4) .25 sec 5) .5 sec 6) 2 sec

need helpp

The expression 16t2 models the distance in feet that an object falls during t seconds after being dropped. Find the distance an object falls during each time.

4) .25 sec 5) .5 sec 6) 2 sec

need helpp

Solution 1

16ft.(.25s)2

4ft/s*2

8ft/s

16ft(.5s)2

8ft/s * 2

16ft/s

16ft(2s)2

32ft/s * 2

64ft/s

ft =feet

s =second(s)

/ =per

4ft/s*2

8ft/s

16ft(.5s)2

8ft/s * 2

16ft/s

16ft(2s)2

32ft/s * 2

64ft/s

ft =feet

s =second(s)

/ =per

Question

Round 157 to the nearest ten

Solution 1

160

because 157 is closer to 160 than 150

because 157 is closer to 160 than 150

Solution 2

If the number you are rounding is followed by 5, 6, 7, 8, or 9, round the number up (+1).

If the number you are rounding is followed by 0, 1, 2, 3, or 4, round the number down (no change).

**15****7**** ≈**** 160**

If the number you are rounding is followed by 0, 1, 2, 3, or 4, round the number down (no change).

Question

Solve for x 3(8x-5)=-4(7-6x)

Solution 1

3(8x - 5) = -4(7 - 6x)

Distribute 3 and -4 inside their respective parentheses.

24x - 15 = -28 + 24x

Add 28 to both sides.

24x + 13 = 24x

Subtract 24x from both sides.

13 = 0

This is an untrue statement, so that means there are no solutions to this equation.

Your answer is **no solution.**

Solution 2

**Answer: **

no solution

**Step-by-step explanation:**

I did this question on my homework and I got it correct

Hope this helps! ;)

Question

Find the midpoint of the segment joining the points: (4, -2) and (-8, 6) Hint: Formula for midpoint is (x1+x2)/2, (y1+y2)/2

Solution 1

[tex](4;-2);\ (-8;\ 6)\\\\the\ midpoint:\left(\frac{4+(-8)}{2};\ \frac{-2+6}{2}\right)\to\left(\frac{4-8}{2};\ \frac{4}{2}\right)\to\left(\frac{-4}{2};\ \frac{4}{2}\right)\to(-2;\ 2)[/tex]

Solution 2

**Answer:**

(-2, 2)

**Step-by-step explanation:**

Look at the image down below!! (ﾉ◕ヮ◕)ﾉ*:･ﾟ✧

Question

What is negative five over eight -5/8 b = 10

Solution 1

[tex]- \frac{5}{8}\cdot b = 10 \ \ \ |multiply\ both\ sides\ by\ (-\frac{8}{5}) \\\\(-\frac{8}{5})\cdot (- \frac{5}{8})\cdot b =(-\frac{8}{5})\cdot 10\\\\b=(-8)\cdot 2\\\\b=-16[/tex]

Question

solve and reduce to lowest term 5 1/2- 2/3

Solution 1

[tex]5 \frac{1}{2}- \frac{2}{3}= 5 \frac{3}{6}- \frac{4}{6}=4\frac{9}{6}-\frac{4}{6}=4\frac{5}{6}[/tex]

Solution 2

5 1/2 - 2/3

11/2 - 2/3

33/6 - 4/6

29/6

11/2 - 2/3

33/6 - 4/6

29/6

Question

Use expressions for odd integers to confirm the conjecture that the product for two odd integers is an odd integer.

Solution 1

2n + 1 et 2n + 3 are two odd integers with n integer

(2n+1)(2n+3) = 4n² + 8n + 3 =2(4n² + 4n) + 3

2(4n² + 4n) is an even integer so 2(4n² + 4n) + 3 is an odd number

because the sum of an even number and an odd number is an odd number.

(2n+1)(2n+3) = 4n² + 8n + 3 =2(4n² + 4n) + 3

2(4n² + 4n) is an even integer so 2(4n² + 4n) + 3 is an odd number

because the sum of an even number and an odd number is an odd number.

Question

What is the answer to this problem and how do you solve it -6=b/18

Solution 1

[tex]-6=\frac{b}{18} \ \ | \ multiply\ both\ sides\ by\ 18\\\\18\cdot (-6)=18\cdot \frac{b}{18}\\\\ 108=b[/tex]

Mathematics
2647929

History
842281

English
748681

Biology
586256

Social Studies
406852

Chemistry
368373

Business
348603

Physics
324927

Health
199835

Spanish
130075

Geography
112100

Computers and Technology
106146

Arts
77164

Advanced Placement (AP)
23675

World Languages
23213

French
22589

Engineering
19607

Law
17108

Medicine
13966

SAT
10987

German
3389

High School
3423409

Middle School
2092250

College
1518097